PENGEMBANGAN E-LKPD BERBASIS ETNOSAINS PADA PEMBELAJARAN EKOSISTEM DI KELAS V SD MENGGUNAKAN MODEL ADDIE - Fitriani, Ida; Dewi, Ratna; Purnamasari, Tika; Anggraini, Nadya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop an Ethnoscience-Based Electronic Student Worksheet (E-LKPD) for ecosystem education in Grade V primary schools. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study focuses on integrating local cultural wisdom into digital learning tools to enhance contextual understanding and engagement. Data collection involved observations, interviews, and expert validations, followed by trials with small and large student groups at SDN 01 and 02 Dwi Warga Tunggal Jaya, Tulang Bawang. Validation results showed the product to be highly feasible, with average ratings above 89%. The trials revealed that the E-LKPD effectively improves student learning engagement, critical thinking, and appreciation for local culture. This research contributes to educational practices by offering an innovative model for integrating ethnoscience with digital learning at the elementary level. Further studies are recommended to explore cross-regional applications and long-term impacts.